Applicable Law in WTO Dispute Settlement: The Imbalance Between Strong International Adjudicative and Weak International Legislative Capacity - Trachtman, Joel (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
This article discusses the historical context of trade and sustainability conflicts and argues that World Trade Organization (WTO) dispute settlement is not equipped to manage these conflicts effectively. Instead, it calls for enhanced international legislative processes to address the complex interactions presented by globalization. It emphasizes the need for integrated and flexible international law-making capabilities to address urgent issues like climate change and biodiversity. It concludes that the WTO must expand its mandate to include sustainable development and cooperate with other international organizations to achieve coherent global welfare.